(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2014)
Currently, there are studies related to yacon, its roots, and leaves; however, research on yacon in fermented beverages, such as yogurt, is very scarce. Therefore, the objective of this study was to investigate the effect of adding yacon concentrate on the physicochemical, microbiological, sensory, and proximate characteristics of yogurt during refrigerated storage. Two treatments were used; one contained yacon concentrate and the other sucrose. During storage, over a period of 30 days, pH, acidity, syneresis, sensory evaluation, lactic acid bacteria (LAB) count, protein, fiber, fat, moisture, ash, and carbohydrates were analyzed.